Investigating the performance characteristics of the barrier discharge ionization detector and comparison to the flame ionization detector for the gas chromatographic analysis of volatile and semivolatile organic compounds. (22nd November 2019) - Antoniadou, Maria; Zachariadis, George A.; Rosenberg, Erwin
Abstract: The response behavior and performance characteristics of the recently introduced barrier discharge ionization detector (BID) for gas chromatography (GC-BID) were investigated by analyzing different classes of organic compounds such as alcohols, alkanes, cycloaliphatic compounds, polycyclic aromatic hydrocarbons (PAHs), and others. The results obtained by GC-BID were compared with those of gas chromatography with flame ionization detection (GC-FID), aiming to demonstrate the particular merits of the new BID detector over the well-established FID. The response of the BID not only was found to be strongly dependent on the detector settings, but also shows a high dependence on the analyte class and the individual analyte. The sensitivity of the BID detector compared to the FID was higher by a factor of ca. 4 on average when considering all compounds analyzed. The relative standard deviation (RSD) was better than 5% for the majority of the cases. The BID detector showed better precision (lower RSD) in comparison with the FID for the investigated compounds. Linear calibrations were obtained for the analytes over more than four orders of magnitude with coefficients of determination typically higher than 0.999 and the limits of detection varied from 0.04 to 1.48 ng/s for the GC-BID.